Analysis Of The Effects Of Communication, Work Facilities, And The Work Environment On Employee Performance At The Office Of Population And Civil Registration In North Padang Lawas - Lubis, Fitria; Yanti, Eli Delvi; Malikhah , Ikhah (Universitas Dehasen Bengkulu, 2026)
This study aims to examine the influence of communication, work facilities, and the work environment on employee performance at the Population and Civil Registry Office in North Padang Lawas. The research method used was quantitative, with multiple linear regression as the data analysis technique, and data processing using SPSS version 23. The sample in this study consisted of 40 employees. Primary data collection used a questionnaire. The results of the study indicate that communication has a positive and significant partial effect on employee performance at the Population and Civil Registration Service in North Padang Lawas, seen from the results of t count > t table (9.239 > 2.028094) with sig. 0.000 < 0.05 so that the results of the study accept H1. Work facilities have a positive and significant partial effect on employee performance at the Population and Civil Registration Service in North Padang Lawas, seen from the results of t count > t table (11.697 > 2.028094) with sig. 0.000 < 0.05 so that the results of the study accept H2. The work environment has a positive and significant partial effect on employee performance at the Population and Civil Registration Service in North Padang Lawas, seen from the results of t count > t table (13.029 > 2.028094) with sig. 0.000 < 0.05 so that the results of the study accept H3. Communication, facilities, and work environment have a significant simultaneous effect on employee performance at the Population and Civil Registry Service in North Padang Lawas, as seen from the results of f count = 101.141 > f table 2.86 with sig. 0.000 < 0.05. Therefore, it can be concluded that H4 is accepted.